Optimasi Ekstraksi Minyak Dan Karotenoid Dari Limbah Serat Mesokarp Kelapa Sawit (incomplete) - Hotman Manurung; Donald Siahaan; Benika Naibaho; Rosnawyta Simanjuntak; Tumiur Gultom (Jurnal Serambi Engineering, 2021)
It is not known how to extract carotenoid- which has a high value -optimally from palm oil  mesocarp fiber (POMF). The research objective was to determine the optimization of oil extraction from POMF waste and to determine the optimization of carotenoid extraction from POMF oil. The research was carried out in 2 stages: The first stage was oil extraction from the POMF with the treatment factor ratio of hexane to the weight of the POMF and the extraction time. Stage 2 Optimization of carotenoid  extraction using the solvolitic method with treatment: Minor solvent types Methyl ester (Me) caprylate-caprate (C8 –C10) and Me laurate-myristate (C12-C14) and minor solvent concentrations of 0.1% and 0, 25%. Parameters analyzed were: oil content, Deterioration bleaching of index (DOBI), and carotenoid concentration. Optimization ratio between hexane and POMF weight is 1:40 (vol / g) with an oil content of 2.938%. Optimization of extraction time for 100 minutes with 4.104% oil content. Optimization of carotenoid extraction is by using minor solvent Me C8-C10 with a solvent amount of 0.1% which results in a carotenoid concentration of 302.442 ppm and DOBI of 5.74. The increase in caroten concentration resulted from saponification reached 114.2 times from the carotenoid concentration in POMF oil.